(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
We investigate the oscillation of class of time fractional partial dierential equation of the form for (x; t) 2 R+ = G; R+ = [0;1); where is a bounded domain in RN with a piecewise smooth boundary @ ; 2 (0; 1) is a constant, D +;t is the Riemann-Liouville fractional derivative of order of u with respect to t and is the Laplacian operator in the Euclidean N- space RN subject to the Neumann boundary condition We will obtain sucient conditions for the oscillation of class of fractional partial dierential equations by utilizing generalized Riccatti transformation technique and the integral averaging method. We illustrate the main results through examples.